2011
DOI: 10.1007/s12011-011-9016-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Accumulation of Calcium and Phosphorus in the Left Coronary Arteries of Thais

Abstract: To examine whether there were gender differences in compositional changes of the coronary artery with aging, the authors investigated the gender difference in age-related changes of elements in the left coronary arteries of Thais by direct chemical analysis. After ordinary dissections by students at Chiang Mai University were finished, the left coronary arteries were resected from Thai subjects. The Thai subjects consisted of 69 men and 34 women. The ages of the male subjects ranged from 25 to 87 years (averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Calcium and phosphate imbalance has been linked to several disorders such as cardiovascular disease, metabolic syndrome, osteoporosis and mortality (1,2,3,4). Some of these conditions display marked sex-specific incidences (3,5,6), which might be related to sex differences in calcium and phosphate homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and phosphate imbalance has been linked to several disorders such as cardiovascular disease, metabolic syndrome, osteoporosis and mortality (1,2,3,4). Some of these conditions display marked sex-specific incidences (3,5,6), which might be related to sex differences in calcium and phosphate homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively small sex differences in serum calcium and phosphate concentrations, our findings may improve our understanding of the underlying pathways for these sex differences. Moreover, our results may be relevant in light of the increasing number of studies showing that serum concentrations of calcium and phosphate in the general populations are related to multiple diseases and mortality 5 , 6 , 12 , 13 . Correcting for albumin in various ways in RS-I-1 has not influenced our findings of sex-based differences in total serum calcium concentrations.…”
Section: Discussionmentioning
confidence: 73%
“…Some of these disorders display marked sex-specific incidences: the incidence of cardiovascular diseases has been found to be lower in women compared to men 5 , 11 . Moreover, Tohno et al found sex differences in the accumulation of calcium and phosphate in coronary arteries 12 . Thus, it is possible that sex differences in the incidence of these disorders might be related to calcium and phosphate homeostasis and that the underlying mechanisms may have clinical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…This finding revealed that the accumulation of Ca and P did not spread from the ascending aorta, aortic valve, or mitral valve to the LC artery. The authors [5] investigated whether there were gender differences in element contents of the LC artery in middle and old ages and found that there were significant gender differences in the accumulation of Ca and P in the LC artery of Thai. The authors [6] also investigated whether age-related changes of elements were different between different sites of the coronary arteries and found that a higher accumulation of Ca and P occurred in the proximal sites of both the LC and the RC arteries compared with the distal sites.…”
Section: Introductionmentioning
confidence: 99%